Anonymous Secure Reputation Routing System For Selective Forwarding Attacks In Wireless Sensor Networks - Dr.V.Thirunavukkarasu, Dr.A.Senthil kumar, K.T.JayaBharathi (International Journal of Advanced Science and Technology, 2020)
Wireless Sensor Networks (WSNs) are more vulnerable to various security threats. One of themost important threat is selective forwarding attacks which maliciously drop a subset of packetswhich are being forwarded hence it makes the resource unavailable to its intended users. Due tothis drop the packet loss rate is high and hence it poses a great challenge to differentiatebetween the normal loss and the malicious drop. In this paper, an anonymous secure routing andreputation system which detects the compromised nodes are combined where the malicious dropcan be identified and reduced. Simulation results demonstrate that anonymous secure reputationrouting system is more efficient than the reputation system. Further this type of authenticatedsecure routing improves the data delivery ratio of the network.